The Influence of Accounting Information System (AIS) on Internal Control in a Company - Lawita, Nadia Fathurrahmi (2020)
This study intends to understand the influence of Accounting Information System (AIS) on internal control in a company that utilizes AIS. This research uses a qualitative research method so the results are presented using descriptive analysis. The discussion in this study explains that the policies and procedures that exist in each company are intended to provide assurance that the intended goals and rules set can be achieved and adhered to, and is a form of management control that is also used to be able to provide reliable financial information and guarantee compliance towards applicable laws and regulations .